2019
DOI: 10.1096/fj.201802637rr
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial activation of leukocyte‐endothelium interaction by fatty acids in the visceral adipose tissue microcirculation

Abstract: High‐fat diet (HFD)‐induced obesity is associated with accumulation of inflammatory cells predominantly in visceral adipose depots [visceral adipose tissue (VAT)] rather than in subcutaneous ones [subcutaneous adipose tissue (SAT)]. The cellular and molecular mechanisms responsible for this phenotypic difference remain poorly understood. Controversy also exists on the overall impact that adipose tissue inflammation has on metabolic health in diet‐induced obesity. The endothelium of the microcirculation regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 97 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…Obesity and its metabolic complications such as type 2 diabetes mellitus (T2DM), pose a threat to global health. 1 However, current anti-obesity drugs cannot provide long-term agreeable outcomes to most obese patients because of limited efficacy and/or substantial adverse effects. 2 Indeed, the classic pharmacotherapy for obesity mainly works through activating anorexigenic effect in central nervous system (CNS) and decreasing fat absorption.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity and its metabolic complications such as type 2 diabetes mellitus (T2DM), pose a threat to global health. 1 However, current anti-obesity drugs cannot provide long-term agreeable outcomes to most obese patients because of limited efficacy and/or substantial adverse effects. 2 Indeed, the classic pharmacotherapy for obesity mainly works through activating anorexigenic effect in central nervous system (CNS) and decreasing fat absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity and its metabolic complications such as type 2 diabetes mellitus (T2DM), pose a threat to global health 1 . However, current anti‐obesity drugs cannot provide long‐term agreeable outcomes to most obese patients because of limited efficacy and/or substantial adverse effects 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and animal studies on inflammatory cascade intervention have demonstrated that inflammation is a contributor to cardiometabolic pathologies [ 105 ]. Inflammatory signaling [ 106 ] and immune cell accumulation [ 116 , 117 , 118 , 119 , 120 ] in adipose tissue cause metabolic dysfunction; however, the initial source of the inflammatory action has remained elusive. Whether the pathogenesis of cardiometabolic disease is initiated by metabolic dysfunction or inflammatory action has long been debated.…”
Section: How Phenotype Flexibility Is Lostmentioning
confidence: 99%
“…It is hypothesized that repetitive nutrient overload is the impetus for cardiometabolic pathogenesis. Lean mice fed single high-fat meals undergo a transient inflammatory response in the visceral adipose tissue that is extended with continued high-fat feeding [ 120 ]. Perhaps the most convincing evidence that the chronic overfed state is responsible for pathogenesis comes from studies employing intermittent fasting.…”
Section: How Phenotype Flexibility Is Lostmentioning
confidence: 99%
See 1 more Smart Citation